INRA's research in industrial biotechnology: For food, chemicals, materials and fuels. (April 2018) - Camarasa, Carole; Chiron, Hubert; Daboussi, Fayza; Della Valle, Guy; Dumas, Claire; Farines, Vincent; Floury, Juliane; Gagnaire, Valérie; Gorret, Nathalie; Leonil, Joëlle; Mouret, Jean-Roch; O'Donohue, Michael J.; et al.
Highlights: Research trends at INRA in food and non-food biotechnologies are presented. Grasping fermentation dynamics is crucial to design food with improved functions. Enzyme, microorganism and microbial consortia are central to non-food biotechnology. Bioprocess engineering development is critical for efficient lab to market transfer. Synthetic biology is emerging as an important sub-area of industrial biotechnology.